Yoga Sebagai Upaya Meringankan Nyeri Haid Pada Remaja Perempuan - wardhani, igustiayu ngurah; Suryanti, Putu Emy (JURNAL YOGA DAN KESEHATAN, 2020)
Every month women aged 12-49 years who are not pregnant and have not yet menopause will experience menstruation. Menstruation is the process of expulsion of blood from the uterus accompanied by uterine lining on women which occurs periodically. During menstruation, many women, especially teenage girls, experience problems with discomfort or pain in the abdomen. Menstrual pain which commonly called dysmenorrhea is a medical condition that occurs during menstruation that can interfere with activities ranging from pain in the abdomen and waist area. There are several ways to relieve dysmenorrhea symptoms, ranging from pharmacological therapy to non-pharmacological therapy. One of the non-pharmacological methods that are often used is yoga. The movements in yoga can strengthen the body and improve blood circulation. During menstruation, mainly the pelvic organs, the perineal and pelvic muscles become healthier and get adequate oxygen intake, so that the vascularity to the reproductive organs becomes optimal. The implementation of yoga, accompanied by trained instructors, is able to provide proper and safe yoga movements to help overcome dysmenorrhea.